Enhancing Student Motivation: Articulate Storyline Learning Media Experiment: Meningkatkan Motivasi Belajar Siswa: Eksperimen Menggunakan Media Pembelajaran Articulate Storyline - Jauharotul Ramadlani Awwalina; Kemil Wachidah (Academia Open, 2023)
This research investigates the impact of utilizing the learning media "Articulate Storyline" on the motivation of fourth-grade students in SDN Sekardangan. Recognizing the prevalence of motivation issues among students, this study employs an experimental approach with a "one group pretest posttest design" to examine the relationship between learning media and student motivation. The data was collected through a social studies learning motivation questionnaire administered to the research sample. The findings demonstrate a significant positive effect of implementing Articulate Storyline on student learning, highlighting its potential as an effective tool for enhancing motivation in educational settings. The implications of these results offer valuable insights for educators and policymakers aiming to foster a conducive learning environment. Highlights: The use of Articulate Storyline learning media significantly enhances student motivation. Experimental study explores the impact of Articulate Storyline on fourth-grade students' motivation. Findings highlight the positive influence of learning media on student motivation. Keywords: Articulate Storyline, learning media, student motivation, experimental study, fourth-grade students.